Justice for Millionaires?. (13th November 2022) - Christensen, James; Parr, Tom; Axelsen, David V.
Abstract: In recent years, much public attention has been devoted to the existence of pay discrepancies between men and women at the upper end of the income scale. For example, there has been considerable discussion of the 'Hollywood gender pay gap'. We can refer to such discrepancies as cases of millionaire inequality . These cases generate conflicting intuitions. On the one hand, the unequal remuneration involved looks like a troubling case of gender injustice. On the other, it's natural to feel uneasy when confronted with the suggestion that multi-millionaires are somehow being paid inadequately. In this paper, we consider two arguments for rectifying millionaire inequality, clarifying their appeal but also identifying the obstacles that each will have to surmount in order to succeed.